TOPICAL ISSUES IN THE DIAGNOSIS AND TREATMENT OF ENDOMETRIOSIS - Palvanova Matlyuba Satvaldievna (Scholar Express Journals, 2023)
The article under discussion reveals endometriosis as an actual problem in gynecological practice. The author of the article considers that endometriosis leads to functional and structural changes in the reproductive system, often adversely affecting the psychoemotional state of women, significantly reducing the quality of life. Diagnosis and treatment of endometriosis depend on the stage and localization of the disease. The choice of treatment depends on the age of the patient, the desire to restore fertility, the severity of symptoms and the extent of the disease
Keywords: endometriosis; gynecological; fertility; reproductive system